Transformation of China’s energy sector: trends and challenges - Lai, Hongyi; Warner, Malcolm (Taylor & Francis, 2014)
The conclusions presented here sum up the contributions in the Special Issue regarding the managing of China's energy sector, particularly regarding the demand and profile of energy as well as the marketization of the sector. Strategic, organizational and policy issues relevant to the main theme are set out. Both demand and supply scenarios for the nation's energy are seen as in flux, as the economy slackens and dependence on imports rises. Unprecedented levels of urban environmental pollution and steady growth of energy consumption in the wake of a rising living standard have brought the issue to headline-prominence as never before. China's rapidly increasing renewable energy will not change its heavy reliance on coal and a lesser extent oil in the coming decade. After decades of transformation, China's energy sector now operates in a domestic market characterized by strong governmental influence and monopolistic state firms. Abroad, China's firms are exposed to heavier market pressure and competition. While the state's policies have succeeded in ensuring energy supplies and propelling China's renewable energy manufacturers into global prominence and opening up domestic market, much room for improvement exists in the competitiveness of the domestic market and domestic energy firms, transparency of pricing and the effectiveness of regulation.